Woman's statement in medicine during the fifteenth and sixteenth century: a religious and inquisitorial process - Sagrario Gómez Cantarino; Catia Filipa Marques Grenha; Filipa Costa Couto; Isabel del Puerto Fernandez; Manuel Moreno Preciado; Manuel Alves Rodrigues (Universidad de Alicante, 2018)
During the fifteenth and sixteenth century, at a time of repression and religious and inquisitorial persecution, women have acted as informal caregivers with empirical practices. The objectives of this article is to emphasize the process of professionalization of women's care over that period and to know the role of the church and men in critical care to women, as well as presenting Spanish female figures who have excelled in medicine during this period. Methods: The task is a narrative review of secondary sources related with the object of study, as well as an analysis of the same sources from the social history, keeping in mind the characteristics of the era of study. Results: During the centuries XV and XVI, the church, along with the medical class, led to a suppression of feminine care that influenced their acceptance. Thus, feminine care generated disagreement and conflict between the church and society and the informal women's care began to be part of the professionalized medical profession. Conclusions: The findings from this study highlight the acceptance of female empirical practices, in contrast to the theoretical knowledge of medical and subsequently the inclusion of women in professional care.